(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the economic consequences of climate change, one of the most pressing global challenges of the 21st century. It highlights the impact of global warming on agriculture, energy, industry, finance, and labor markets, with particular attention to developing countries. The paper emphasizes the necessity of sustainable development, the transition to a green economy, and the collective responsibility of governments, institutions, and society to mitigate risks. The findings underline that climate change is not only an environmental problem but also an economic threat that requires urgent global cooperation.